PEMBERDAYAAN MASYARAKAT MISKIN DALAM PENGUSAHAAN MAKANAN TERNAK SAPI - KUSRIANI PRASETYOWATI (JURNAL ILMIAH AGRINECA, 2014)
This aim of this research is to detect what elucidation hits cow livestock food supplying especially hit bulrush cultivation can be poor society especially village Gedongan. The method that used in this research is social research method for considering and repair planning, monitoring effectiveness and efficiency and welfare programs and other humanity service. Population in this case society at village Gedongan that has cow livestock and can plant bulrush at also yard or divider rice field. While sample from chosen according to random/not expressly to given elucidation hits cow livestock food supplying especially bulrush power mind. This data is gatherred to pass interview or direct observation at watchfulness location. data source in this research primary data and secondary data. Based on research result shows that with elucidation as society enableness process is process self-support society, permanent self-supporting will open self from side aid that believed will give benefit. Old ones delay time existence between moment first hear a innovation with period does adoption. While impact from supplying elucidation program eats cow livestock really always there, the positive impact coordination various elucidation activity is easier,Â  but the negative impact also there among others elucidation likes this more has top down and less join in society participation in elucidation program activity planning, globally cow livestock food supplying elucidation program can be said success.